2014 International Conference on Interactive Collaborative Learning (ICL) 2014
DOI: 10.1109/icl.2014.7017768
|View full text |Cite
|
Sign up to set email alerts
|

Expert vs. novice: Problem decomposition/recomposition in engineering design

Abstract: The purpose of this research was to investigate the differences of using problem decomposition and problem recomposition among dyads of engineering experts, dyads of engineering seniors, and dyads of engineering freshmen. Fifty participants took part in this study. Ten were engineering design experts, 20 were engineering seniors, and 20 were engineering freshmen. Participants worked in dyads to complete an engineering design challenge within an hour. The entire design process was video and audio recorded.After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Participants are typically presented with an intersection they are familiar with, and they are asked to include any relevant diagrams and assumptions they made during their design (Adams et al, 2003;Atman and Bursic, 1996;Cardella et al, 2002;Cardella et al, 2008;Roberts et al, 2007). • In the window problem participants design a device which could provide assistance to a person with a disability to open a stuck, double-hung window without relying on electric power (Gero et al, 2013;Kannengiesser & Gero, 2017;Lammi & Gero, 2011, Lammi, 2011Song & Becker, 2014;Wells et al, 2016;Williams et al, 2012). This specific task can be attempted by fairly novice designers.…”
Section: Design Taskmentioning
confidence: 99%
“…Participants are typically presented with an intersection they are familiar with, and they are asked to include any relevant diagrams and assumptions they made during their design (Adams et al, 2003;Atman and Bursic, 1996;Cardella et al, 2002;Cardella et al, 2008;Roberts et al, 2007). • In the window problem participants design a device which could provide assistance to a person with a disability to open a stuck, double-hung window without relying on electric power (Gero et al, 2013;Kannengiesser & Gero, 2017;Lammi & Gero, 2011, Lammi, 2011Song & Becker, 2014;Wells et al, 2016;Williams et al, 2012). This specific task can be attempted by fairly novice designers.…”
Section: Design Taskmentioning
confidence: 99%
“…While each of these methods produced interesting results, the most promising method is protocol studies. It has become the basis of the current cognitive study of designers (Atman, et al 2008;Badke-Schaub et al 2007;Becker & Mentzer, 2012;Christensen & Schunn 2007;Gericke, et al 2007;Gero, Kan & Jiang, 2014;Kavakli & Gero, 2002;McDonnell & Lloyd, 2007;McNeill, et al, 1998;Song, 2014;Suwa, et al, 1998;Suwa, Gero & Purcell, 2000;Williams, et al, 2013).…”
Section: Design Cognition Researchmentioning
confidence: 99%
“…FBS Processes This project builds on previous NSF-funded projects that looked at the longitudinal development of design cognition of undergraduate engineering students across two contiguous years (Williams, Lee, Gero & Paretti, 2013). Results from a pilot study at Utah State University show there is a significant gap between the cognitive behavior of novice and professional expert engineering designers (Song, 2014). This project makes use of those results and focuses on gaps.…”
Section: Table 1 Fbs Codesmentioning
confidence: 99%
“…Building on previously NSF-funded projects that looked at the longitudinal development of design cognition of undergraduate engineering students across two contiguous years (Williams, Lee, Gero & Paretti, 2013), this research seeks to further understand undergraduate student design cognition, but more importantly, to establish an inventory of expert design cognition. Results from a pilot study at a western land-grant university show there is a significant gap between the cognitive behavior of novice and professional expert engineering designers (Song, 2014). Additionally, a meta-analysis of design cognition studies indicated that there are commonalities, as well as differences, between students and professional designers (Gero, Kannengiesser & Pourmohamadi, 2012).…”
Section: Design Cognition Researchmentioning
confidence: 99%
“…Cognitive studies fall into five main methodological categories: protocol studies, interviews (Cross & Cross, 1998), input-output experiments; where the designer is treated as a black box which produces the behaviors in the outputs for changes in inputs (Purcell, Williams, et al, 1993), anthropological studies (Lopez-Mesa & Thompson, 2006), and questionnaires. While each of these methods produce intriguing results, protocol studies have become the basis of the current cognitive study of designers (Atman, et al 2008;Badke-Schaub et al 2007;Becker & Mentzer, 2012;Christensen & Schunn 2007;Gericke, et al 2007;Gero, Kan & Jiang, 2014;Kavakli & Gero, 2002;McDonnell & Lloyd, 2007;McNeill, et al, 1998;Song, 2014;Suwa, et al, 1998;Suwa, Gero & Purcell, 2000;Williams, et al, 2013).…”
Section: Design Cognition Researchmentioning
confidence: 99%